2019
DOI: 10.1021/acsbiomaterials.8b01420
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione (GSH) Peptide Conjugated Magnetic Nanoparticles As Blood–Brain Barrier Shuttle for MRI-Monitored Brain Delivery of Paclitaxel

Abstract: In drug delivery science, brain delivery is one of the most important challenges because of the low efficiency of the available treatments. Nowadays, shuttle peptides have attracted more attention because of lower price, reduced immunity, and increased chemical capability. Glutathione (GSH) is one of the blood−brain barrier (BBB) shuttle peptides that has reached the most progressive steps in the path toward clinical application. This project discovered the possibility of GSH-conjugated IONPs as an MRI-monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 31 publications
(45 reference statements)
0
23
0
Order By: Relevance
“…Also, utilization of certain ligands, such as transferrin, can benefit for targeted therapy and the penetration of biological barriers such as the BBB and cell membranes. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Also, utilization of certain ligands, such as transferrin, can benefit for targeted therapy and the penetration of biological barriers such as the BBB and cell membranes. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…The hemolytic activity of NPs was less than 3% at 10 mg ml −1 (Table ). Since samples with hemolytic activity of less than 3% are known as safe samples, Fe 3 O 4 @BSA‐MTX NPs are safe and applicable in the biomedical field. Photographs of HRBCs incubated with positive and negative controls and synthesized Fe 3 O 4 @BSA‐MTX NPs at concentrations of 1, 5 and 10 mg ml −1 are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Nosrati et al (2019) reported the use for glutathione (GSH) decorated iron NPs (GSHIONPs) for brain drug delivery. IONPs@Asp-PTX-PEG-GSH are stable, non-toxic and enhance MRI contrast for diagnostic purpose [111].…”
Section: Metallic Npsmentioning
confidence: 99%